Minat organisasi pada mahasiswa: bagaimana peran resiliensi akademik dan dukungan sosial orang tua? - Nurmala, Vina Rizka; Matulessy, Andik; Suhadianto, Suhadianto (SUKMA : Jurnal Penelitian Psikologi, 2024)
Organizational interest is an individual's interest in an activity and has the desire to contribute to an organization. This study aims to determine the relationship between academic resilience and parental social support and organizational interest in students. This research method uses quantitative correlation with the number of respondents as many as 384 active students in Surabaya which was taken by accidental sampling technique. The research scale uses the interest scale taken from the Crow and Crow (2005) aspect, the academic resilience scale is adapted from the Cassidy scale (2016) and the parental social support scale uses the Sarafino and Smith (2011) aspect. The results showed that there was a significant positive relationship between academic resilience and parental social support and organizational interest in students. From the results of the partial test, there was a significant positive relationship between academic resilience and organizational interest in students and there was a significant positive relationship between parental social support and organizational interest in students.